Amyloid-β1-42 dynamically regulates the migration of neural stem/progenitor cells via MAPK-ERK pathway. (25th January 2019) - Wang, Zhu; Chen, Yantian; Li, Xueyi; Sultana, Pinky; Yin, Ming; Wang, Zejian
Abstract: Neural stem/progenitor cell (NSPC) based therapy represents an attractive treatment for Alzheimer's disease (AD), the most common neurodegenerative disorder with no effective treatment to date. This can be achieved by stimulating endogenous NSPCs and/or administrating exogenously produced NSPCs. Successful repair requires the migration of NSPCs to the loci where neuronal loss occurs, differentiation and integration into neural networks. However, the progressive loss of neurons in the brain of AD patients suggests that the repair by endogenous NSPCs in the setting of AD may be defective. The production and deposition of amyloid-β1-42 (Aβ1-42 ) peptides is thought to be a central event in the pathogenesis of AD. Here we report that Aβ1-42 peptides inhibit the migration of in vitro cultured NSPCs by disturbing the ERK-MAPK signal pathway. We found that the migratory capacity of NSPCs was compromised upon treatment with oligomeric Aβ1-42 ; the inhibitory effect occurred in a dose-dependent manner. Our previous studies have shown that Aβ1-42 triggers the expression of GRK2 by unknown mechanism. Herein we found that the Aβ1-42 evoked upregulation of GRK2 expression was attenuated upon treatment with the ERK inhibitor SCH772984 at 2.5 μM, but not with inhibitors for p38 or JNK. We detected a dose-dependent increase in levels of phosphorylated ERK1/2 after incubation of cells with oligomeric Aβ1-42 peptides for 3 days. We observed that an increase in the phosphorylation of p38 and JNK coincided with reduced phosphorylation of ERK1/2 upon treatment with Aβ1-42 for 6 and/or 9 days. We hypothesize that the divergence of the activation of the MAPK family of pathways may contribute to the inhibition of NSPCs migration after the long-term incubation with Aβ1-42 . Pretreatment with 1 μM MEK inhibitor U0126 reversed the effects of Aβ1-42 on GRK2 expression of and NSPC migration. Together, our results suggest that Aβ1-42 oligomers compromise the migratory capacity of NSPCs through the MEK-ERK pathway. Highlights: Amyloid-β suppressed the migration and augmented the expression of GRK2 in NSPCs. ERK was activated by Aβ1-42 after a short-term incubation. Whereas, ERK was inactivated by Aβ1-42 after a long-term incubation. Inhibitor of MEK-ERK reversed the high expression of GRK2 induced by Aβ1-42 . Inhibitor of MEK-ERK reversed the decreased migration of NSPCs induced by Aβ1-42.